Sosialisasi “FlowFit” Gerakan Simpel untuk Meningkatkan Kesehatan Sistem Kardiovaskular Ibu PKK Desa Karangan Kecamatan Karanganom Kabupaten Klaten - Kholisna, Arin; Kumalasari, Eni; Nuraini, Habibah; Brata, Nugroho Trisnu; Hendratna, Hendratna (Jurnal Bina Desa, 2024)
The decrease in physical activity and unhealthy lifestyles cause people in the pre-elderly and elderly age groups to experience various health problems. These problems are experienced by residents of Karangan Village, especially housewives who complain of symptoms of cardiovascular system disorders. This community service program aims to increase awareness and knowledge about the importance of maintaining healthy blood flow through the socialization and education of simple movements called "FlowFit". The socialization was carried out at the Village PKK forum, PKK Dukuh Grubugan RW 8, and PKK Dukuh Nglumbang Kramat and Karang Lor RW 11. The methods applied in the socialization included lectures, demonstrations, and discussions with PKK mothers. The media used were interactive power points, distribution of pamphlets and showing video tutorials so that participants could easily understand the information conveyed by the speakers. Participants in the activity gave a positive impression and were full of enthusiasm. The results of the FlowFit socialization activity were able to increase public awareness to maintain a healthy cardiovascular system through the implementation of simple movements that can be practiced independently. There were 85% of participants who stated that they understood the importance of this movement and planned to implement it in their daily lives. With the socialization of FlowFit, it is hoped that it will be able to reduce the risk of cardiovascular disease in residents of Karangan Village.